Production of Bioethanol from Waste Potatoes - Mohammed, Alaa Kareem; Ali, Safaa Abalrassol; Jiyad, Jameel Hadi (Al-Khwarizmi Engineering Journal, 2014)
In this research, production of ethanol from waste potatoes fermentation was studied using Saccharmyses cerevisiae. Potato Flour was prepared from potato tubers after cooking and drying at 85°C. Homogenous slurry of potato flour was prepared in water at solid liquid ratio 1:10. Liquefaction of potato flour slurry with α-amylase at 80°C for 40 min followed by saccharification with glucoamylase at 65°C for 2 hr .Fermentation of hydrolysate with Saccharomyces cerevisiae at 35°C for two days resulted in production of 33 g/l ethanol.      The parameters studied were; temperature, time of fermentation and pH. It was found that Saccharification process is affected by enzyme Amylo 300 concentration and concentration of 1000µl/100ml gives efficient effect of the process. The best temperature for fermentation process was found to be about 35oC. Also it was noticed that ethanol production was increased as time of fermentation increased but after 48 hr further increase in fermentation time did not have appreciable effect. Finally, the optimal value of pH for fermentation process was about 5 to 6.